Updated functional annotation of the Mycobacterium bovis AF2122/97 reference genome. Issue 7 (30th July 2020) - Farrell, Damien; Crispell, Joseph; Gordon, Stephen V.
Abstract : Mycobacterium bovis AF2122/97 is the reference strain for the bovine tuberculosis bacillus. Here we report an update to the M. bovis AF2122/97 genome annotation to reflect 616 new protein identifications that replace many of the old hypothetical coding sequences and proteins of unknown function in the genome. These changes integrate information from functional assignments of orthologous coding sequences in the Mycobacterium tuberculosis H37Rv genome. We have also added 69 additional new gene names.